Her daughter's dream [compact disc, unabridged] - Rivers, Francine, 1947- (Rivers, Francine, 1947- Marta's legacy, 2010)
Just as Carolyn had formed a stronger bond with her Oma Marta than with her mother, so Carolyn's daughter is drawn to her grandma more than to a mom who's caught up in the 1960s counterculture.